2015
DOI: 10.1353/jda.2015.0134
|View full text |Cite
|
Sign up to set email alerts
|

Households’ characteristics and the modes of remittances in Bangladesh

Abstract: The modes of remittances of households in Bangladesh have been categorised as 'No Remittances', 'Internal Remittances' and 'International Remittances'. This paper using a Multinomial Logit Model studies the associations between these modes and the households' basic characteristics. The study reveals that household level variables like rural-urban locations, age and sex of the households heads, religion, ratio of male, adult and young members etc. are potentially significant in households' orientation to remitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Size, for example, tends to increase the financial burden of a family, thus negatively impacting the ability of that household to use the internet. Again, the specific results of the households related variables in the specification agree with previous empirical outcomes such as the studies by Delgado and Miles (1997), Chowdhury (2015) Castree ( 2016), and Chen et al (2018) on the importance of the characteristics of household on their earning potentials According to the findings, overseas remittances have a significant impact on households' ability to access and use the internet in Nigeria. However, compared to other finance options available to a family, the amount of influence is negligible.…”
Section: Discussionsupporting
confidence: 85%
“…Size, for example, tends to increase the financial burden of a family, thus negatively impacting the ability of that household to use the internet. Again, the specific results of the households related variables in the specification agree with previous empirical outcomes such as the studies by Delgado and Miles (1997), Chowdhury (2015) Castree ( 2016), and Chen et al (2018) on the importance of the characteristics of household on their earning potentials According to the findings, overseas remittances have a significant impact on households' ability to access and use the internet in Nigeria. However, compared to other finance options available to a family, the amount of influence is negligible.…”
Section: Discussionsupporting
confidence: 85%
“…Salim 1992;Ahmed 1993;Chowdhury 1992;Ahmad & Zohora 1997;Rahman 1999). Mannan & Farhana 2014a, 2014b, 2014c, 2014dMannan et al 2014;Masuduzzaman 2014;Chowdhury 2015;Pradhan 2015;Mannan & Farhana 2015a, 2015b, 2015cMannan & Fredericks 2015Akter 2016Azam et al 2016;Haider et al 2016;Hassan et 2016;IOM 2010Islam & Rayhan 2016;Majumder 2016;Osmani 2016aOsmani , 2016bRashid 2016;Regmi & Paudel 2016;Taguchi & Lama 2016;Hassan & Shakur 2017;Mahmud 2017Mahmud , 2014Siddiqui 2016Siddiqui , 2004bWadood & Hossain 2017;Ahmed et al 2018;Ghelli 2018;Kumar et al 2018;Sarkar et al 2018;Kumar 2019;Mannan 2017aMannan , 2017bMannan , 2017cMannan , 2016Mannan , 2015Mannan , 2011aMannan , 2011bRahman et al 2020)…”
Section: Resultsmentioning
confidence: 99%
“…Hatemi‐J and Uddin () found that poverty reduction and remittances in Bangladesh affect each other. Chowdhury () utilised HIES 2010 data to associate households' characteristics with the mode of remittances in Bangladesh. Although the possibility of existence of other studies cannot be excluded, it appears that the amount of studies on migration and remittances in Bangladesh is rather limited relative to the position of Bangladesh in terms of migration and remittances in the world economy.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…We regard the religion of the household the same as the religion of the head. For a detailed description of how the variables have been constructed using the survey data, see Chowdhury ().…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation